Fruit characterization of five genotypes of tacaco [Sechium tacaco (Pittier) C. Jeffrey] in Costa Rica - Monge-Pérez, José Eladio (2017)
Tacaco fruits of five high quality genotypes were characterized in Costa Rica, both at qualitative (three variables) and quantitative (10 variables) levels. There were statistically significant differences between genotypes for quantitative variables. Data show a wide variability with respect to fruit weight (31,55 – 40,30 g), fruit length (57,36 – 63,61 mm), fruit width (39,72 – 41,57 mm), fruit thickness (28,01 – 30,40 mm), number of complete fruit longitudinal sutures (5,11 – 5,61), number of incomplete fruit longitudinal sutures (0,22 – 1,61), number of fruit spines (0 – 22,36), fruit length/width ratio (1,42 – 1,53), fruit length/thickness ratio (1,92 – 2,21), and fruit width/thickness ratio (1,36 – 1,45). These genotypes could be good choices for growers and consumers that demand high quality tacaco fruits. This is the first notice about the existence of tacaco fruits with six and seven complete longitudinal sutures, and with two to five incomplete longitudinal sutures; this could illustrate the recent evolutive changes of this species.